Intercropping of different vegetables and field spices with brinjal (Solanum melongena) - Prasad, K S; Mohan, N K (The Indian Journal of Agricultural Sciences, 2012)
A 2 year field experiment was conducted during winter season of 1991-92 and 1992–93 to study the performance of brinjal (Solallum melollgena L.) as a main crop and its intercropping with ’Pusa Desi’ radish (Raphanus salivus L.), ’Pusa Parvati’ french bean (Phaseolus vulgaris L), ’White Vienna’ knolkohl (Brassica oleracea L. var gongylodes L.), â€˜Methi 47’ fenugreek (Trigermala foenum- graecum L.) and local coriander (Coriandrum salivum L.). The highest yield of brinjal (16.23 (onnes/ha) was recorded in the monocrop (brinjal alone), followed by brinjal + french bean (16.08 tonnes/ha). In terms of benefit; cost ratio, brinjal + french bean intercropping was most remunerative (1.99).